Ki-67 expression in pulmonary tumors—reply - Kriegsmann, Mark; Warth, Arne (Translational Lung Cancer Research, 2016)
First of all, we would like to congratulate Professor Chirieac for his excellent discussion on proliferation assessment in lung tumors. Taken together, he concludes that assessment of proliferation is important for the prognosis of non-small cell lung cancer (NSCLC), prediction of brain metastases in patients with lung adenocarcinoma, and the diagnosis, classification and prognosis of pulmonary neuroendocrine tumors but is subjective, has a poor reproducibility, and is depended on laboratory techniques—which is more or less in line with our opinion as well as our own data (1-4).
Gesehen am 28.05.2020